Bacillus thuringiensis: a short revision - Polanczyk, R.; Alves, S. (Agrociencia Uruguay, 2003)
In this review are discussed some aspects related to the entomopathogenic bacterium Bacillus thuringiensis. This includes its interaction with the environment and insects and with more details its action mode, nomenclature, characterization and utilization in the pest management context. To conclude, it was discussed the possible deleterious effects of this microrganism in the environment and non target organisms.